Chapitre IV. La multiplicité des voix narratives - Chapuis, Sophie (Presses Sorbonne Nouvelle, 2018)
Reading The Rifles may be quite a chaotic experience for those who expect a smooth journey through the legends of Captain Franklin and his crew. There can be no doubt that William T. Vollmann’s project is not that of writing a historical novel. Combining fiction with historical events, the writer challenges any categorization of his book. To quote his own terms, Vollmann wants to offer his reader a “symbolic history”, which is more akin to a vision than a historical account; a collection of tales narrated by a teller rather than a historian. Questioning the relation between history and truth, Vollmann is concerned with the way literature mediates the past. As a way to protest against a one-way perspective on history, the author suggests parallel and fictitious discourses on the past. The point of this chapter is to prove that these variations on the past are made possible by the constant confusion and multiplication of narrative voices.As a background to his experiment, Vollmann chooses Captain Franklin’s fourth expedition to the Arctic, a XIXth -century outline which constantly collides with the XXth-century narrative of John Subzero, a Franklin epigone who is merely wandering about the ice shelf, spending some of his nights with an Inuit girl named Reepah. Trying to evade both time and space, Vollmann chooses the Arctic setting to allow the possibility for history to be reinvented on these white and virgin lands. The image of melting ice is also frequently used as a metaphor for the short-lived voices that decline soon after they are heard.To prove how dangerous a unique perspective on history can be, Vollmann first embodies what he means to decry. In the first pages, the author is omniscient, exercising a full control over his characters in a godly manner. However, his authority gradually fades away so that in the end, Vollmann, the author, enters the world of his own fiction to become Vollmann, a character. This inherent dichotomy rules over the composition of the whole novel which is mainly built on a ...